Anisamide-functionalized pH-responsive amphiphilic chitosan-based paclitaxel micelles for sigma-1 receptor targeted prostate cancer treatment. (1st February 2020) - Qu, Ding; Jiao, Mengying; Lin, Haijiao; Tian, Chunli; Qu, Guowei; Xue, Jingwei; Xue, Lingjing; Ju, Caoyun; Zhang, Can
Graphical abstract: Highlights: Anisamide-conjugated N-octyl-N, O-maleoyl-O-phosphoryl chitosan (a-OPMPC) features with targeting ability and pH sensitivity. a-OPMPC can self-assembled into micelles for solubilization of paclitaxel (PTX). PTX loaded a-OPMPC micelles (PTX-aM) can effectively deliver PTX to prostate cancer cells via sigma-1&anisamide affinity. PTX-aM can rapidly release PTX in endo/lysosomes with acidic environment. PTX-aM exhibited improved antitumor efficacy against prostate cancer. Abstract: Controlled release and tumor-selective distribution are highly desirable for anticancer nanomedicines. Here, we design and synthesize an anisamide-conjugated N -octyl- N, O -maleoyl- O -phosphoryl chitosan (a-OMPC) which can form amphiphilic micelles featuring pH-responsive release and high affinity to sigma-1 receptor-overexpressed tumors for paclitaxel (PTX) delivery. Thereinto, maleoyl and phosphoryl groups cooperatively contribute to pH-responsive drug release due to a conversion from hydrophile to hydrophobe in the acidic microenvironment of endo/lysosomes. We demonstrated that PTX-loaded a-OMPC micelles (PTX-aM) enhanced the cellular internalization via the affinity between anisamide and sigma-1 receptor, rapidly released drug in endo/lysosomes and elevated the cytotoxicity against PC-3 cells. The in vivo studies further verified that PTX-aM could largely accumulate at the tumor site even after 24 h of administration, resulting in obvious inhibition effect and prolonged survival period in PC-3 tumor xenograft-bearing mice. Moreover, OMPC showed no obvious hemolytic and acute toxicity. Collectively, this chitosan derivate holds a promising potential in application of prostate cancer-targeted drug delivery system.